ANALISIS TEBAL LAPIS TAMBAH DAN UMUR SISA PERKERASAN AKIBAT BEBAN BERLEBIH KENDARAAN (STUDI KASUS RUAS JALAN NASIONAL DI PROVINSI SUMATERA BARAT) - ', Suriyatno; ', Purnawan; Putri, Elsa Eka (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
Due to limited availability of vehicle load data, estimator often use standard load in order tocalculate the pavement thickness and overlay course thickness. This certainly makes thecalculation of pavement thickness and overlay course thickness become not accurate. Inaccuratecalculation results less capability of the pavement to endure the traffic load, as of the pavementbecome damaged before it reach it life service as planned. The aim of this study is to calculateoverlay course thickness of flexible pavement based on actual load, standard load and remaininglife service. The standard load that has been used based on form letter (Surat Edaran) DirectorateGeneral of Perhubungan Darat, Department of Public Works No. 2, 2008. The actual load wasobtained by vehicle load survey using Portable Weighter instrument. Overlay course thicknesswas calculated using Manual Design of Pavement No. 02/M/BM/2013. The study case wasconducted on four road segments, those are Tanah Badantung – Kiliran Jao road, Batas KotaPadang – Kota Painan road, Batas Provinsi Riau – Payakumbuh road and Sicincin – LubukAlung road. The traffic load estimation shows that the actual traffic load is greater than standardload. This results the overlay course thickness based on actual load is greater than the overlaycourse thickness based on the standard load. The greater distinction is on Tanah Badantung –Kiliran Jao load, wherein the thickness of overlay course that results by actual load is 56.4%greater than the thickness of overlay course that results by standard load. The greater traffic loadalso results reduction on pavement life service. Due to overloading, life service of TanahBadantung - Kiliran Jao road is reduces 56.8 % of 5 years life service (2 years and 10 months).Kata kunci: Overlay, Overload Vehicle, Remaining Life.